Majority of symptoms in esophageal reflux PPI non‐responders are not related to reflux. Issue 11 (4th September 2015) - Roman, S.; Keefer, L.; Imam, H.; Korrapati, P.; Mogni, B.; Eident, K.; Friesen, L.; Kahrilas, P. J.; Martinovich, Z.; Pandolfino, J.E.
Abstract Background Genesis of persistent gastro‐esophageal reflux symptoms despite proton pump inhibitor (PPI) therapy is not fully understood. We aimed at determining reflux patterns on 24‐h pH‐impedance monitoring performed on PPI and correlating impedance patterns and symptom occurrence in PPI non‐responders. Methods Seventy‐eight PPI non‐responder patients underwent 24‐h pH‐impedance monitoring on PPI. Reflux impedance characterization included gastric and supragastric belches and proximal extent of reflux. Symptoms were considered associated with reflux if occurring within 5 min after a reflux event. Patients were classified into three groups: persistent acid reflux (acid esophageal exposure [AET] >5% of time), reflux sensitivity (AET <5%, symptom index [SI] ≥50%), and functional symptoms (AET <5%, SI <50%). Dominant impedance pattern was determined for each patient. Key Results Seven patients (9%) had persistent acid reflux, 28 (36%) reflux sensitivity, and 43 (55%) functional symptoms. A total of 4296 reflux events were identified (median per patient 45 [range 4–221]). Although liquid reflux was the most common pattern in all groups, patients with reflux sensitivity and functional symptoms had much more variability in their pattern profile with a large proportion being associated with gastric and supragastric belching. Only 417 reflux events (9.7%) were associated with symptoms. Reflux with a supragastric component and proximal extent were more likely to be associated with symptoms. Conclusions & Inferences The impedance reflux profile in PPI non‐responders was heterogeneous and the majority of reflux events were not associated with symptoms. Thus, the treatment of PPI non‐responders should focus on mechanisms beyond reflux, such as visceral hypersensitivity and hypervigilance.